Overexpression of sarcoendoplasmic reticulum calcium ATPase 2a promotes cardiac sympathetic neurotransmission via abnormal endoplasmic reticulum and mitochondria Ca(2+) regulation. - Shanks, J; Herring, N; Johnson, E; Liu, K; Li, D; Paterson, D (American Heart Association, 2017)
Reduced cardiomyocyte excitation–contraction coupling and downregulation of the SERCA2a (sarcoendoplasmic reticulum calcium ATPase 2a) is associated with heart failure. This has led to viral transgene upregulation of SERCA2a in cardiomyocytes as a treatment. We hypothesized that SERCA2a gene therapy expressed under a similar promiscuous cytomegalovirus promoter could also affect the cardiac sympathetic neural axis and promote sympathoexcitation. Stellate neurons were isolated from 90 to 120 g male, Sprague–Dawley, Wistar Kyoto, and spontaneously hypertensive rats. Neurons were infected with Ad-mCherry or Ad-mCherry-hATP2Aa (SERCA2a). Intracellular Ca2+ changes were measured using fura-2AM in response to KCl, caffeine, thapsigargin, and carbonylcyanide-p-trifluoromethoxyphenylhydrazine to mobilize intracellular Ca2+ stores. The effect of SERCA2a on neurotransmitter release was measured using [3H]- norepinephrine overflow from 340 to 360 g Sprague–Dawley rat atria in response to right stellate ganglia stimulation. Upregulation of SERCA2a resulted in greater neurotransmitter release in response to stellate stimulation compared with control (empty: 98.7±20.5 cpm, n=7; SERCA: 186.5±28.41 cpm, n=8; P<0.05). In isolated Sprague–Dawley rat stellate neurons, SERCA2a overexpression facilitated greater depolarization-induced Ca2+ transients (empty: 0.64±0.03 au, n=57; SERCA: 0.75±0.03 au, n=68; P<0.05), along with increased endoplasmic reticulum and mitochondria Ca2+ load. Similar results were observed in Wistar Kyoto and age-matched spontaneously hypertensive rats, despite no further increase in endoplasmic reticulum load being observed in the spontaneously hypertensive rat (spontaneously hypertensive rats: empty, 0.16±0.04 au, n=18; SERCA: 0.17±0.02 au, n=25). In conclusion, SERCA2a upregulation in cardiac sympathetic neurons resulted in increased neurotransmission and increased Ca2+ loading into intracellular stores. Whether the increased Ca2+ transient and neurotransmission after SERCA2A overexpression contributes to enhanced sympathoexcitation in heart failure patients remains to be determined.